2003
DOI: 10.1136/jnnp.74.7.962
|View full text |Cite
|
Sign up to set email alerts
|

Similarity and disparity of obsessive-compulsive disorder and schizophrenia in MR volumetric abnormalities of the hippocampus-amygdala complex

Abstract: Objectives: Given that obsessive-compulsive disorder (OCD) and schizophrenia may share clinical symptoms as well as functional brain abnormalities, this study was designed to clarify common and different morphological abnormalities in OCD and schizophrenia. Methods: Volumes of the hippocampus, the amygdala, and the thalamus were measured in three age and sex matched groups of 22 patients with OCD, 22 patients with schizophrenia, and 22 normal subjects using three dimensional magnetic resonance imaging. Volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 13 publications
6
50
0
4
Order By: Relevance
“…The finding of larger left compared to right amygdala volume in our sample of medication-free patients is consistent with the results of Kwon et al (2003), who reported significantly larger left amygdala volume in their sample of OCD patients compared to patients with schizophrenia and healthy volunteers. These findings may have relevance for a prior study that reported smaller amygdala volume in previously treated adults with OCD compared to healthy comparison subjects (Szeszko et al, 1999).…”
Section: Discussionsupporting
confidence: 81%
“…The finding of larger left compared to right amygdala volume in our sample of medication-free patients is consistent with the results of Kwon et al (2003), who reported significantly larger left amygdala volume in their sample of OCD patients compared to patients with schizophrenia and healthy volunteers. These findings may have relevance for a prior study that reported smaller amygdala volume in previously treated adults with OCD compared to healthy comparison subjects (Szeszko et al, 1999).…”
Section: Discussionsupporting
confidence: 81%
“…One of the brain structures which has been a focus of research is the hippocampal formation. Magnetic resonance (MR)-based in vivo measurement of hippocampal volume is an accepted technique, which has been performed in the aged 1 and healthy subjects, 2 and has revealed a number of structural abnormalities in a variety of neurological and psychiatric disorders, such as temporal lobe epilepsy, 3 Huntington's disease, 4 Turner's syndrome, 5 Cushing's disease, 6 Down's syndrome, 7 Alzheimer's disease (AD), 8 mild cognitive impairment, 9 schizophrenia, 10 major depression (MD), 11 bipolar disorder, 12 post-traumatic stress disorder (PTSD), 13 borderline personality disorder, 14 chronic alcoholism, 15 obsessive-compulsive disorder, 16 and panic disorder. 17 The MR-derived hippocampal volumetric technique has demonstrated good validity and reproducibility, [18][19][20] and accuracy of the measurements has been shown by MRI volumetric measurement of phantoms with a known volume.…”
mentioning
confidence: 99%
“…Clinical symptoms in OCD also involve fear conditioning and the association of external stimuli with emotion, suggesting involvement of the hippocampus 131 and amygdala. 37 Both structures have been implicated in OCD, 10,81,104 although not in all cases. 20,170 In the section on PD, hyperdirect pathways connecting the motor cortex with the STN play an important role in the ability of aberrant oscillatory propagation between cortex and basal ganglia structures.…”
Section: Mechanistic Understandingmentioning
confidence: 99%